Oxidative balance scores and gallstone disease: mediating effects of oxidative stress - HaoPeng Zhu; Lei Jin; Zhe Zhang; Chao Lu; QiTao Jiang; YiPing Mou; WeiWei Jin (Nutrition Journal)
Abstract Background Gallstone disease (GSD) is a prevalent gastrointestinal disorder, few studies have examined the combined effects of dietary and lifestyle factors on GSD. This study aims to investigate the relationship between oxidative balance score (OBS) and GSD, and explores the potential mediating role of oxidative stress. Methods Cross-sectional data from 6,196 participants in the NHANES 2017–2020 were analyzed. OBS, encompassing 16 dietary and 4 lifestyle factors, was assessed alongside GSD prevalence. Weighted multivariate logistic regression, restricted cubic spline (RCS) analysis were used to explore the relationship between OBS and GSD and mediation analysis was used to test the indirect effect of oxidative stress indicators. Subgroup analysis and sensitivity analysis were used to determine the stability of results. Results A higher OBS was significantly associated with a reduced risk of GSD (OR: 0.701, 95% CI: 0.492–0.999, P < 0.05). RCS analysis revealed a linear association between OBS and GSD risk. Mediation analysis indicated significant mediating effects of albumin and uric acid, with a combined mediation proportion of 19.540% (P < 0.05). Subgroup analysis revealed differences and interrelationships based on education level, providing additional insights into the relationship between OBS and GSD and sensitivity analysis confirmed the stability of these associations. Conclusions A higher OBS is associated with a reduced risk of GSD, especially among higher education levels groups, and albumin, uric acid may act as mediators of this association. These findings underscore the potential role of oxidative stress in GSD and the significance of maintaining a healthy diet and lifestyle to decrease GSD risk.